2000
DOI: 10.1007/s003470050001
|View full text |Cite
|
Sign up to set email alerts
|

Cataracta secundaria

Abstract: The different ocular conditions of the anterior and posterior segment showed a different profile for Nd:YAG laser capsulotomy energy level and Nd:YAG laser repetition rate. Sulcus fixation of an IOL resulted in earlier capsulotomies with higher energy levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Auffarth et al analysed energy levels of Nd: YAG laser capsulotomy for secondary cataracts in a series of 172 patients and found that the total laser energy was significantly higher with sulcus fixated IOL’s. [ 17 ] This observation was similar to the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Auffarth et al analysed energy levels of Nd: YAG laser capsulotomy for secondary cataracts in a series of 172 patients and found that the total laser energy was significantly higher with sulcus fixated IOL’s. [ 17 ] This observation was similar to the results of the present study.…”
Section: Discussionsupporting
confidence: 93%